The sabah rhino breeding programme : reproductive management of the critically endangered Sumatran rhinoceros of Borneo (Dicerorhinus sumatrensis harrissoni) as conducted by the IZW-Berlin between 2005 and 2015 - Fiúza, Ana Rafaela Barbosa de Lima (2017)
Dissertação de Mestrado Integrado em Medicina Veterinária